Two-dimensional geoelectrical modeling using a Rayleigh-Fourier method - Osella, Ana Maria (2000)
In this paper, we present a new method for DC resistivity modeling as an alternative to finite element and finite difference techniques, based on a Rayleigh-Fourier approach. This is especially adequate to model 2-D layered structures with smooth irregular boundaries. The validity of the method is verified by comparing its results with FE solutions for two synthetic models, representing a horst and a graben. The ability to model actual data has also been tested by applying it to interpret data from tectonic basin in the Sierras Pampeanas region in Argentina. During the modeling process, the method showed good convergence and proved friendly to use. Several layers could be identified as being part of an aquifer complex, and the most remarkable fact regarding the reliability of the results is that the description of these layers is in good agreement with information from wells.